Kamsel Unit Management in Implementing Dikmas Lantas to Minimize Car Accidents at Temanggung Polres - Bhawana, I Dewa Gde (Advances in Police Science Research Journal, 2024)
The high number of freight car accidents in the jurisdiction of the Temanggung Police has become a problem in traffic which has resulted in enormous material losses and has had an impact on the people’s economy. It is the duty and responsibility of the National Police to deal with this problem by carrying out preventive efforts through Dikmas Lantas by the Kamsel Unit Traffic Unit of the Temanggung Police. This study aims to analyze the management of the Kamsel Unit in carrying out Dikmas Lantas to minimize the number of freight car accidents at the Temanggung Police Station. This research was conducted in the jurisdiction of the Temanggung Police, Central Java. This study uses a qualitative approach and field research methods. Data collection was carried out through interviews, observation, and document studies. Technical data analysis was used, namely data collection, data reduction, data presentation, and conclusion. This paper uses conceptual literature including the concept of Dikmas Lantas, the concept of traffic accidents, the concept of goods cars, Perkap number 1 of 2019, management theory, and social communication theory. The results of the study showed that there were several obstacles in the Management of the implementation of direct community education by the Kamsel Unit of the Temanggung Police to minimize the number of freight car accidents. Deficiencies were found related to the organizational resources owned and the management of the implementation of the appropriate Dikmas Lantas had not been implemented. To deal with this, the author provides several suggestions to optimize the implementation of Dikmas Lantas such as utilizing radio media as a means of implementing Dikmas Lantas, making traffic appeals in the form of permanent billboards, and carrying out periodic outreach to the Temanggung area freight car association. Apart from that, cooperation was carried out with the Polsek ranks to expand the reach of the implementation of Dikmas Lalu for goods cars.